Den oväntade kärleken: Om otrohet - Abnersson, Veronica; Lundgren, Anna Sofia (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
Adultery is not easy to discuss. Women with experience of adultery often, when they are to talk about it, see a necessity to compare their experiences with what they mean is the dominant view on the phenomenon. Important themes that came up during the interviews dealt with a felt disagreement of the "institutionalized" or "common" morality, the embodiment of feelings, and the discursive practice of adultery. The women call the often condemned view of adultery into question, but they also reproduce this view and let it inform both their experiences and the way in which they look upon themselves as individuals, women, wives and mothers.